Enhancing Students' Learning Motivation Through Wordwall as an Interactive Learning Tool in Class XII.G at SMAN 1 Pinrang - Fadhilah Aulia Suhardi; Jusman Tang; sam hermansyah .; Selviana Putri; Safridah Safridah; Nova Azis; Haikal Syahrir (Edumaspul: Jurnal Pendidikan, 2024)
This study investigates the effectiveness of Wordwall, an interactive learning tool, in enhancing students' learning motivation in Class XII.G at SMAN 1 Pinrang. The research was conducted using a classroom action research (CAR) methodology, consisting of two cycles of planning, action, observation, and reflection. Data were collected through pre-tests and post-tests, classroom observations, and student questionnaires to assess the impact of Wordwall on students' motivation and academic performance. The results showed a significant improvement in student engagement, participation, and motivation, with students actively involved in learning activities and showing greater enthusiasm in the classroom. The use of Wordwall increased students' intrinsic motivation by providing an enjoyable and dynamic learning environment. These findings suggest that integrating interactive learning tools like Wordwall can foster a more engaging classroom atmosphere and improve learning outcomes.